Anticonvulsant activity of 3,5-dimethylpyrazole derivatives in animal models - KAYMAKÇIOĞLU, BEDİA; ONAT, FİLİZ; GÜLHAN, REZZAN (SPRINGER BIRKHAUSER, 2011)
A series of 3,5-dimethylpyrazole derivatives, structurally related to the previously described potent ameltolide analogues, were synthesized and evaluated for their anticonvulsant activity. Ten compounds were prepared by reacting the 4-amino-3,5-dimethylpyrazole with appropriate substituted carboxylic acids, benzoyl chlorides and benzaldehydes to obtain amide and imine derivatives. Initial anticonvulsant screening was performed using intraperitoneal pentylenetetrazole (PTZ) and maximal electroshock (MES) induced seizure tests in mice. Among the 10 tested compounds, N-[1-(4-methoxybenzoyl)-3,5-dimethylpyrazole-4-yl]-4-methoxybenzamide 2 and N-[1-(2,6-dichlorobenzoyl)-3,5-dimethylpyrazole-4-yl]-2,6-dichlorobenzamide 3 decreased seizure severity and the mortality rate in the PTZ test. Hence, compound 3 was tested in an animal model of absence epilepsy, Genetic Absence Epileptic Rats from Strasbourg (GAERS). There were no significant changes in the duration or number of spike-and-wave discharges in this model.
Keywords: 3,5-Dimethylpyrazole; Amide; Imine; Anticonvulsant activity; ANALOGS; SENSITIVITY; AMELTOLIDE